Local convergence for multi-point-parametric Chebyshev–Halley-type methods of high - Argyros, Ioannis K; George, Santhosh; Magreñán, Á. Alberto (Journal of Computational and Applied Mathematics, 2017)
We present a local convergence analysis for general multi-point-Chebyshev-Halley-type methods (MMCHTM) of high convergence order in order to approximate a solution of an equation in a Banach space setting. MMCHTM includes earlier methods given by others as special cases. The convergence ball for a class of MMCHTM methods is obtained under weaker hypotheses than before. Numerical examples are also presented in this study. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: banach space; multi-point; multi-parametric method; Chebyshev-Halley methods; local convergence; radius of convergence; JCR; Scopus